Pengembangan Media Pembelajaran CD Tutorial Interaktif Pada Mata Pelajaran Simulasi Digital - Maisiswati, Baiq Hartina; Ismatulloh, Kholida; Uska, Muhammad Zamroni (Jurnal Pendidikan Informatika (EDUMATIC), 2018)
The purpose of this study is (1) to determine the development of instructional CD learning media on digital simulation subjects in class X at 1 Sakra Vocational High School; (2) to find out the feasibility of media experts and material experts on learning CD tutorial media products; (3) to find out the students' response to the development of tutorial CD learning media on digital simulation subjects in class X at Sakra Vocational High School 1. This type of research uses R & D (Reseach and Development) development methods. The subjects of this study were class X TKJ as many as 20 students. Data collection in the form of interviews, questionnaires, and observations. Data analysis techniques use quantitative and qualitative data. The results showed that the learning media tutorial CD developed was very valid for use in the learning process. From the media expert validation for the media, the tutorial CD was declared to be very feasible because it had an average percentage of 92%, while the validation of material experts had an average percentage of 91%, and for students' responses it was said to be very good because it had an average percentage of 90%, so that it can be said that the Tutorial CD learning media is effectively used in the learning process at SMK 1 Sakra